Access to International Plant Sciences Journals - An Endangered Species? - Kathy Fescemyer (Issues in Science and Technology Librarianship, 2004)
Access to international resources is always challenging. This project measures the availability of international journals in the plant sciences in libraries in the United States. The availability of 189 journals was evaluated by searching WorldCat. The analysis showed that 55% of the titles were held in 20 or fewer libraries throughout the United States. A subset of 16 titles searched in 30 libraries showed that only 57% of the libraries maintained current subscriptions to the journals. Implications to the lack of accessibility to these materials by North American researchers are discussed with suggestions of how availability might be improved.